What does the image of an idealized union conceal? Beatriz Ñusta and the fall of the Inca Empire in four colonial paintings - Artzi, Bat-ami (2024)
This article analyzes four colonial paintings from the Viceroyalty of Peru that depict the union of Beatriz Ñusta and Martín de Loyola, as well as the marriage of their daughter. From a feminist perspective, it explores the pictorial and historical representations of Beatriz Ñusta and the possible connections between them. The iconographic analysis presented in this article highlights the agency of the Indigenous or mestizo artists who created these paintings. Furthermore, the study of the iconographic differences found in these paintings, as well as a metal plaque that represents part of the scene, reveals variations related to the audiences for which these artworks were intended.